Impact of the iCODEX tool in routine clinical practice in Spain. (1st February 2022) - Gómez-Antúnez, María; Recio-Iglesias, Jesús; Almagro, Pere; Díez-Manglano, Jesús; López-García, Francisco; Boixeda, Ramon
Abstract: Introduction: The prognosis of COPD patients can be calculated using multidimensional indexes that improve the predictive capacity of the individual variables. The CODEX index can be calculated using iCODEX, a digital support tool available on the web and in an app. The aim of this study was to evaluate how the usefulness and applicability of iCODEX and its recommendations in routine clinical practice are perceived by specialists in internal medicine, pneumology, and primary care. Methods: A cross-sectional study was conducted from November 2019 to February 2020 with the participation of specialists in internal medicine, primary care, and pneumology. All respondents completed a survey consisting of 104 questions on their perception of the iCODEX tool. Results: Overall, 335 physicians responded. Of these, 95.2% had no difficulty accessing the tool and 83.1% were quite or very satisfied with it. Regarding the applicability and implementation of iCODEX recommendations in routine clinical practice, respondents reported that the recommendations were generally applicable: most questions obtained a median score of ≥ 4 out of 5. The recommendations with the greatest expected clinical benefit are listed. Conclusions: Our study shows that the iCODEX tool is easy for participating specialists to use and identifies the recommendations that have the greatest clinical impact in areas such as lung obstruction, severe exacerbations, exercise, smoking, and patient follow-up.